ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI JAGUNG HIBRIDA DI KECAMATAN SEI BINGEI KABUPATEN LANGKAT - Supristiwendi Supritiswendi; Abdul Rahman; Endang Sari Simanullang (JURNAL AGRICA, 2018)
Subdistrict Sei Bingei as a place in this study with the reason that the District Sei Bingei Corn is the largest production center and is one of the areas of hybrid maize cultivation area in Langkat.This study uses field observations using a questionnaire and interview research instruments, this kind of research is quantitative deskiptif. The population in this study were all farmers who harvest corn hybrids available in three (3) sample villages in the district Bingei Sei. Data analysis model that is used is multiple regression analysis estimated the Cobb Douglas production function.The results of this study are : In the test can be proved that the simultaneous influence of land area variable (X1), seeds (X2), labor (X3), fertilizer (X4) and herbicides (X5) is very significant to the variable production of hybrid corn. Then on a separate effect test 1) land area (X1) , seeds (X2) and herbicides (X5) significantly affects the production of hybrid corn. 2) labor (X3) and fertilizer (X4) does not significantly affect the production of hybrid corn. Conclusion : The independent variables are: land area (X1), seeds (X2), labor (X3), fertilizer (X4) and pesticides (X5) can explain the dependent variable Y (hybrid maize production) of 72.5%. The rest 27.5% is explained by the factors of production are not included in the regression models of this study. The elasticity of production and scale of 2,113 hybrid corn farming. Keywords: Production, Model Estimation, Corn Hybrids